Pemerintahan Berbasis Elektronik (E-Government) dan Pembangunan Berkelanjutan: Reviu Literatur Sistematis: Reviu Literatur Sistematis - Faturachman Alputra Sudirman; Saidin Saidin (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
The development of e-government is a positive determinant for a country to achieve sustainable development, including social and environmental economic development. Through the process of inclusion and exclusion, this study determined that 52 articles published in peer-reviewed journals from the Scopus database from 2015 to 2021 were to be reviewed or systematically reviewed. This study uses the Systematic Literature Review (SLR) method to identify, summarize, review and relate thoughts from previous research. From the SLR, it is known that e-government has a significant influence on sustainable development, such as improving good governance, controlling corruption, and the effectiveness of government management, which is faster, easier, and cheaper, as well as being able to encourage e-participation of the community that increases the possibility to achieve sustainable development, especially in developing countries. However, this study also concludes that implementing e-government services to contribute to sustainable development faces obstacles and challenges such as the availability of ICT platforms and inadequate infrastructure, budget constraints, human resource capacity, and government support. The great attention to the issue of e-government and sustainable development is due to e-government having direct and indirect effects on environmental and socio-economic sustainability.